Functional assessment of athletes of different specialization - Фаворитов [Volodymyr Favouritov], Володимир Миколайович; Гостіщев [Wadim Gostishev], Вадим Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
Were the features of the aerobic and anaerobic performance of athletes of different specialization age 18-22 years. Evaluation of the survey was carried out in shifts of physiological parameters with the use of rapid assessment. The analysis of functional training athletes of different specialization at the end of the preparatory phase. Athletes showed different potential of the aerobic and anaerobic capacity, due to the specifics of the sport. It is shown that the use of modern monitoring system functional training athletes contributed to a significant objectification of data on the overall level of fitness athletes. The study results recommend the development of a monitoring system to practical use when working with sportsmen of high qualification.